Persepsi Masyarakat Terhadap Karakter Fisik dan Spasial Kota yang Mengalami Efek Urban Heat Island - Farhan Ramadhan; Dewi Larasati; Hanson Endra Kusuma; Roiswahid Dimas Pangestu (Arsir: Jurnal Arsitektur, 2025)
Climate change and rapid urbanization have heightened the need for effective Urban Heat Island (UHI) mitigation strategies to foster sustainable urban development. This study examines public perceptions of UHI and the physical-spatial characteristics of cities affected by it, an area that has not been extensively explored in relation to demographic factors. Using an open questionnaire survey, demographic data, awareness, and community responses to UHI from 119 respondents were analyzed qualitatively with a Grounded Theory approach, employing open coding techniques. The objective of this study is to identify patterns of relationships between demographic factors, public perceptions, and knowledge regarding UHI. The findings revealed that 31% of respondents identified insufficient vegetation as the primary cause of UHI, followed by high building density (30%) and fossil fuel-based activities (17%). Education level was found to significantly influence awareness, with individuals holding a master's degree (S2) exhibiting 19% higher awareness compared to those with a bachelor's degree (S1). Public perceptions were also influenced by geographical distribution, with 68% of respondents residing in Bandung. The study also identified nine key physical-spatial characteristics associated with UHI, including limited vegetation, air pollution, and inadequate shading. Three major challenges were identified: insufficient public education on UHI, weak communication between researchers and policymakers, and limited implementation of data-driven mitigation strategies at the municipal level. The conclusions drawn from this study provide valuable insights for developing more inclusive, data-driven policies and emphasize the importance of community involvement in designing cities that are resilient to climate change and the impacts of UHI.